2017
DOI: 10.1177/0194599817723609
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Guideline: Evaluation of the Neck Mass in Adults Executive Summary

Abstract: The American Academy of Otolaryngology-Head and Neck Surgery Foundation has published a supplement to this issue of Otolaryngology-Head and Neck Surgery featuring the "Clinical Practice Guideline: Evaluation of the Neck Mass in Adults." To assist in implementing the guideline recommendations, this article summarizes the rationale, purpose, and key action statements. The 12 recommendations developed emphasize reducing delays in diagnosis of head and neck squamous cell carcinoma; promoting appropriate testing, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…16,17 For this reason, diagnostic FNA is still recommended as the first diagnostic test before proceeding to open neck biopsy. 12 Fortunately, recent research confirms that FNA can accurately diagnose lymphoma when there is close coordination between the head and neck surgeon and an experienced cytopathologist and when cytomorphology is supplemented by modern flow cytometry. 18,19 While additional tissue collection in the form of core needle biopsy or open biopsy is often recommended after FNA results suggest lymphoma, 20 other pathologies must first be ruled out by the FNA, hence the emphasis on FNA as the first-line diagnostic measure.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…16,17 For this reason, diagnostic FNA is still recommended as the first diagnostic test before proceeding to open neck biopsy. 12 Fortunately, recent research confirms that FNA can accurately diagnose lymphoma when there is close coordination between the head and neck surgeon and an experienced cytopathologist and when cytomorphology is supplemented by modern flow cytometry. 18,19 While additional tissue collection in the form of core needle biopsy or open biopsy is often recommended after FNA results suggest lymphoma, 20 other pathologies must first be ruled out by the FNA, hence the emphasis on FNA as the first-line diagnostic measure.…”
Section: Discussionmentioning
confidence: 93%
“…In our regional cohort, we found that 31 of 50 or 62% of patients fall in this category. Despite patient care guidelines that advise against open neck mass biopsy, this procedure is still being used as a primary diagnostic test for some patients. In assessing clinical documentation stating why surgeons conducted an open biopsy, the majority (26/50 or 52%) use vague terms and cite non‐evidence–based findings, such as cystic neck mass, as indications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations